KOMPETENCJA MIĘDZYKULTUROWA – KONCEPCJE I WYZWANIA - Siek-Piskozub, Teresa (Neofilolog, 2018)
One of the goals of foreign language education is to prepare learners to the role of intercultural mediators, as indicated in such documents as National Standards for Foreign Language Education or The Common European Framework of Reference for Languages. Research on culture and its relation to language has a long tradition and reveals a complex and also dynamic nature of the concept. Culture has also been present, although to a different extent, in the long practice of foreign language teaching. However, our understanding of cultural competence in a multicultural and multilingual European Union, which sets goals in the area of education in its Member States, has been evolving. In the article we will discuss different concepts of culture proposed by such researchers as Hofstede (1980, 1991), Binnett (1993), Weaver (2001), and Byram (1997), as well as various concepts of approaching culture in the foreign language education context. We will also look at challenges faced by Polish learners and teachers in the foreign language classroom.